NK cells are associated with immunometabolic response to a single exercise exertion in heart failure patients. (3rd October 2022) - Swaminathan, K; Koc, A; Kaczmarek, S; Lehnert, K; Urbaneck, I; Domanska, G; Landmesser, U; Felix, S B; Doerr, M; Bahls, M; Kraenkel, N
Abstract: Background: Increased systemic inflammation and metabolic dysfunction are observed in heart failure with reduced ejection fraction (HFrEF). On the other hand, cardiorespiratory exercise testing (CPET) exerts a physical challenge and initiates the activation of the immune system, including acute release of natural killer (NK) cells into the circulation, and several metabolic pathways. Aim: To characterize the inflammatory and metabolic alterations of HFrEF patients in response to an acute exercise challenge, and after 2 hours of recovery. Methods: Participants with HFrEF (n=16), age and sex matched controls (CON, n=13) were investigated at baseline, immediately after and 2 hours after CPET. Clinical and physiological parameters, leukocyte profile, plasma cytokines and metabolites were assessed along with inflammatory and metabolic parameters at all three time points. NK cell counts and morphological/activation parameters in different contexts were examined. Further, the time-dependent coordination of NK cell numbers post-exercise with tryptophan metabolism and plasma triglycerides were assessed. NK cells were isolated from blood of healthy donors for ex vivo proof-of-principle experiments, including phenotype polarization and NK cell specific tryptophan metabolism. Results: Cardiovascular risk profiles as well as leukocyte, cytokine and metabolic parameters at baseline were similar in CON and HFrEF. Immediately after CPET, lactate, and NK T cell blood counts were significantly increased in both groups. In HFrEF but not CON, platelet aggregates with NK cells, CD8+ cytotoxic T cells and "classical" CD14++CD16-monocytes, phosphatidylcholines and triglycerides were increased. After 2h of recovery, almost all altered parameters returned to baseline in CON. In contrast, blood counts and morphological markers of inflammatory effector cell types, including CD8+ T cells and neutrophils remained elevated in HFrEF. NK cells remained elevated after the recovery period and correlated with levels of various triglyceride species in the HFrEF patients. Tryptophan levels in plasma were reduced by acute exercise and the kynurenine to tryptophan ratio was increased and correlated with increase in NK and NK-T cell counts, as well as IL-12 plasma levels. Treatment with IL-12 led to increased synthesis of kynurenine from tryptophan, expression of indoleamine 2, 3-dioxygenase and abundance of regulatory CD56bri NK cell phenotypes ex vivo. Secretome of untreated NK cells impaired cellular respiration, increased glycolysis/oxidation ratio in skeletal muscle cells, and increased the release of triglycerides from hepatocarcinoma cells. Conclusion: CPET induced a complex acute immunometabolic response, whose restitution to baseline levels differed between HFrEF and healthy controls. Exercise-induced changes in NK cell metabolism and phenotype shift might modulate cellular respiration in myocytes and release of triglycerides by hepatocytes in HFrEF and in CON. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DZHK (German Centre for Cardiovascular Research)